DEVELOPING THE SUBSTANCE OVER FORM DOCTRINE IN TAXATION AFTER THE JUDGEMENT IN COMMISSIONER FOR THE SOUTH AFRICAN REVENUE SERVICE v NWK (The Pretoria Student Law Review, 2021)
In 1936 Lord Tomlin in IRC v Duke of Westminster (hereafter ‘Duke’)1 concluded that it is trite law that every man (and woman) is entitled to arrange his or her affairs as to pay the least amount of tax under the appropriate statutes. This sentiment has been a cornerstone of South African tax jurisprudence and was again repeated in Commissioner for the South African Revenue Service v NWK Ltd (hereafter ‘NWK’).2 This broad liberty in arranging one’s own tax affairs has, however, led some taxpayers to dress up their transactions and hide their’ true nature as to ‘either … secure some advantage which otherwise [the law] would not give, or to escape some duty which otherwise the law would impose’.3 The most prominent tool the courts can use to try and curb this type of abuse is the General Anti-Avoidance Rules (hereafter ‘GAAR’) in Section 80A to 80L of the Income Tax Act 58 of 1962 (hereafter ‘the Act’), other specific anti-avoidance provisions in the Act4 and the substance over form doctrine (hereafter ‘the doctrine’). This article is a reflection on the taxation in South Africa, but specifically anti-avoidance provisions as provided by legislation.
Keywords: Lord Tomlin in IRC v Duke of Westminster; anti-avoidance; South African tax jurisprudence